2020
DOI: 10.5194/acp-2020-140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What have we missed when studying the impact of aerosols on surface ozone via changing photolysis rates?

et al.

Abstract: Previous studies have emphasized that the decrease in photolysis rate at the surface induced by the light extinction of aerosols could weaken ozone photochemistry and then reduce surface ozone. However, quantitative studies have shown that weakened photochemistry leads to a much greater reduction in the net chemical production of ozone, which does not 15 match the reduction in surface ozone. This suggested that in addition to photochemistry, some other physical processes related to the variation of ozone shoul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Because the VMIX contribution to the ground is closely dependent on the vertical gradient of the concentration and the turbulence exchange coefficients (Gao et al 2020). To confirm why the VMIX contribution to the surface ozone As shown, the gradient of vertical profile of accumulative CHEM contribution on 6 July was significantly larger than that of vertical profiles of accumulative CHEM contribution on 5 July and 7 July (Fig.…”
mentioning
confidence: 86%
“…Because the VMIX contribution to the ground is closely dependent on the vertical gradient of the concentration and the turbulence exchange coefficients (Gao et al 2020). To confirm why the VMIX contribution to the surface ozone As shown, the gradient of vertical profile of accumulative CHEM contribution on 6 July was significantly larger than that of vertical profiles of accumulative CHEM contribution on 5 July and 7 July (Fig.…”
mentioning
confidence: 86%
“…In addition to the photolysis impacts of aerosols on ozone, aerosols also influence surface ozone concentration via atmospheric dynamic effects: (1) changing the concentrations and configurations of precursors, and (2) affecting the vertical exchange of ozone (Hansen et al, 1997;Gao et al, 2018;Yang et al, 2021). Previous studies have analyzed atmospheric dynamic effects using numerical models such as WRF-Chem (Gao et al, 2020;Qu et al, 2020;An et al, 2021). With the aim of addressing this issue based on observation data, wintertime data were also used to show the dynamic atmospheric effects of aerosols on ozone.…”
Section: Responses Of Surface Ozone To Aerosol Scattering and Absorptionmentioning
confidence: 99%
“…Many studies have revealed that aerosols affect ozone by changing the photolysis frequency (Jacobson et al, 1998;Benas et al, 2013;Wang et al, 2019), some studies have quantified the impacts of absorbing aerosols on surface ozone (Li et al, 2005;Mok et al, 2016;An et al, 2021), and recent studies have compared the differences in the impacts of scattering and absorbing aerosols on ozone (Gao et al, 2022;Shi et al, 2022). Aerosols also absorb oxidative radicals, inhibit the formation of ozone in the troposphere (Jacob et al, 2000;Lou et al, 2014;Li et al, 2018), and influence ozone by altering atmospheric dynamics, that is, affect the evolution of the atmospheric boundary layer and the vertical exchange (Xing et al, 2017;Gao et al, 2020;Yang et al, 2021). Studies have shown that high concentrations of ozone promote the generation of secondary aerosols by enhancing atmospheric oxidation, thereby increasing the risk of haze events (Fu et al, 2020;Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Scattering‐dominate aerosols (i.e., sulfate, nitrate, and organic carbon) enhance shortwave radiation (SW) in the upper part of the BL but weaken it near the surface (Liao et al., 1999), leading to an increase in the photolysis rate, acceleration of photochemical reactions, and promotion of ozone formation above the BL (Dickerson et al., 1997). Highly absorbing aerosols (i.e., black carbon (BC) and dust) reduce the ozone concentration in the whole troposphere due to decreasing the J[NO 2 ] (Gao et al., 2020). In addition, absorbing aerosols can induce heating in the upper BL and depress the vertical mixing of pollutants (Ding et al., 2016; Lu, Lu, et al., 2020), weakening the entrainment of ozone from the top of the BL to the surface in the morning (Gao et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…whole troposphere due to decreasing the J[NO 2 ] (Gao et al, 2020). In addition, absorbing aerosols can induce heating in the upper BL and depress the vertical mixing of pollutants (Ding et al, 2016;, weakening the entrainment of ozone from the top of the BL to the surface in the morning (Gao et al, 2018).…”
mentioning
confidence: 99%